The Influence of GCG, Leverage, And Profitability on Corporate Investment With Economic Policy Uncertainty As A Moderating Variable - Narendraputra, Faiz; Utami, Wiwik (Dinasti Publisher, 2025)
This study examined the influence of good corporate governance, leverage, and profitability on corporate investment, with economic policy uncertainty as a moderating variable. The population consisted of companies classified within the energy sector and listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, totaling 82 companies. The sample selection process employed purposive sampling, resulting in a final sample of 51 companies. This study utilized secondary data obtained from the Indonesia Stock Exchange (www.idx.co.id). Panel data regression analysis was conducted using EVIEWS 12 software. The results indicated that, collectively, good corporate governance, leverage, and profitability influenced corporate investment. Partially, leverage and profitability had a significant positive effect on corporate investment, whereas good corporate governance and economic policy uncertainty did not have a significant effect. The moderating variable, economic policy uncertainty, did not moderate the relationship between good corporate governance and profitability, while leverage was negatively moderated by economic policy uncertainty.